Typical and Atypical Enteroaggregative Escherichia coli Are Both Virulent in the Galleria mellonella Model - Guerrieri, Caroline Gastaldi; Pereira, Monalessa Fábia; Galdino, Anna Clara Milesi; Santos, André Luis Souza dos; Elias, Waldir Pereira; Schuenck, Ricardo Pinto; Spano, Liliana Cruz (Frontiers in Microbiology, 2019)
Enteroaggregative Escherichia coli (EAEC) is an emerging pathotype responsible for acute and persistent diarrhea. It can be classified as typical and atypical strains, respectively, based on the presence or absence of the AggR regulon, suggesting a higher virulence for typical EAEC. This study aimed to evaluate in the Galleria mellonella model if there are differences in the virulence profiles among clinical strains of typical and atypical EAEC, prototype strains EAEC C1096, 042 and its aggR mutant. The clinical EAEC strains (n= 20) were analyzed for the presence of 22 putative virulence factors of EAEC or extraintestinal E. coli by PCR, as well as phenotypic characteristics of virulence (enzymes, siderophore and biofilm). The survival of the larvae was analyzed after inoculation of 104 to 107 CFU/larva; the monitoring of bacterial growth in vivo and hemocyte quantification was determined after inoculation of the prototype strains (105 CFU/larva) at different periods after infection. The strains of typical and atypical EAEC presented the same virulence profile for the larva, regardless of the amount or type of genes and phenotypic aspects of virulence analyzed. In addition, the EAEC 042 aggR mutant strain showed a significant reduction in the mortality of the inoculated larvae compared to the wild-type strain. In conclusion, the results obtained herein demonstrate that the virulence of EAEC seems to be related to the AggR regulon, but not exclusively, and atypical EAEC strains may be as virulent as typical ones in vivo in the G. mellonella model.